AI and the Metaverse for Retailers: Chances, Limitations, and Managerial Recommendations in 2024 - Diego Borgo; Michael Hoang (Marketing Review St.Gallen, 2024)
Diego Borgo is a Web3 and Metaverse advisor, guiding Fortune 500 companies into the Metaverse and NFT space, including Adidas ("Into the Metaverse"), Shell, and Skoda. In the interview, he shines light on the recent significant metaverse and AI developments. He emphasizes that while the metaverse is still in its early stages, it represents the next evolution of digital connectivity, adding a 3D layer to our interactions. Meanwhile, AI has already had its breakthrough moment, with its understanding and adoption growing exponentially. Borgo's insights highlight the rapid pace of change in these fields and the need for clear understanding and ethical considerations as the technologies continue to evolve.
Keywords: 650